2018
DOI: 10.1021/acs.macromol.8b00301
|View full text |Cite
|
Sign up to set email alerts
|

High Proton Conduction of Organized Sulfonated Polyimide Thin Films with Planar and Bent Backbones

Abstract: Fast proton conduction was achieved in organized lamellar structures with in-plane oriented structure parallel to the substrate surface using a lyotropic liquid-crystalline (LC) property. Alkyl sulfonated polyimides (ASPIs) with bent main chain structure were newly synthesized to investigate relations between the higher order structure and proton transport properties. Proton conductivity of all polyimide thin films was greater than 10–2 S/cm. Grazing-incidence small-angle X-ray scattering (GI-SAXS) revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…Recently, Ono and co-workers discussed the influence of rigidity and planarity of the main chain structure in ASPI thin films (Figure 5(d)) [101]. Earlier studies showed interchain packing for the lamellar structure as suppressed by steric effects of nonplanar and bent backbones of polyimides without sulfonic acid group [102].…”
Section: Highly Proton-conductive Polymer Thinmentioning
confidence: 98%
See 2 more Smart Citations
“…Recently, Ono and co-workers discussed the influence of rigidity and planarity of the main chain structure in ASPI thin films (Figure 5(d)) [101]. Earlier studies showed interchain packing for the lamellar structure as suppressed by steric effects of nonplanar and bent backbones of polyimides without sulfonic acid group [102].…”
Section: Highly Proton-conductive Polymer Thinmentioning
confidence: 98%
“…ASPI thin film with high molecular weight exhibited higher molecular order and higher proton conductivity than that with low molecular weight. (d) Schematic of influence of rigidness and planarity of the main chain to the organized structure in ASPI thin films Proton conductivity with planar backbone was higher than that with bent backbone [101]. Reprinted with permission from Ono et al [101].…”
Section: Highly Proton-conductive Polymer Thinmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they are limited by their low operation temperature, high cost, and high fuel crossover [9,10,11]. To address the problems, sulfonated nonfluoroniated aromatic materials, such as poly(phenylene)s [12,13], polyphenylenes [14], polyimides [15], poly (arylene ether sulfone) [16,17], and poly (ether ether ketone) (SPEEK) [18] have been proposed with good chemical/thermal stability, low cost, and high mechanical stability. However, poor hydrophilic/hydrophobic phase separation and insufficient proton conductivity were reported [19,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Recently, aromatic hydrocarbon membranes have been developed for their low methanol permeability, excellent mechanical properties and low cost. 8,9 Typical representatives including sulfonated polyimide (SPI), [10][11][12][13] sulfonated poly (arylene ether ketone) (SPEEK). [14][15][16] sulfonated poly (arylene ether sulfone) (SPAES) [17][18][19][20] and sulfonated polybenzimidazole 21,22 are used as PEM.…”
Section: Introductionmentioning
confidence: 99%